KEDUDUKAN MAJELIS ULAMA INDONESIA (MUI) DAN KOMISI FATWANYA DALAM SISTEM HUKUM TATA NEGARA - Mujaid Kumkelo (lp2m-uin malang, 2010)
This paper contains the research of two issues on law as follows 1) the juridical normative and substantive position of MUI and its fatwa (instruction) commission (KFHMUI) in the constitutional law system and 2) the influence of the fatwa issued by KFHMUI on the government policy on the fatwa of KFHMUI. Elaborating primary, secondary and tertiary law sources through historical approach carries out this juridical normative research. Jimly Assiddiqie categorizes state institutions in the constitution into three parts. The first is called the high state institutions (LTN). The second part is the institutions that function to support the prime roles, whose authority in constitution 1945 only by implication not assertively defined. The last is state institution that is not mentioned in the constitution, but only mentioned in the parliamentary laws. These institutions are categorized into constitutional importance. The result indicates that, the Indonesian Ulema Council (MUI) is neither explicitly categorized as a reflection of islamic institution, nor precisely recognized in the constitution for its authority and even its name. Above all, however, there are some findings of this research: first, the position of MUI and its fatwa commission in constitutional law can be found through historical approach. Second, state institution will have stronger legitimation in formulating its policy or regulation related to Moslems by taking into account, considering, and positioning the institutions of the religion fatwa reviewer as a co partner in law forming and public policy making.